2016
DOI: 10.1136/jclinpath-2015-203447
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based-limited and personalised education management maximise appropriateness of vitamin D, vitamin B12 and folate retesting

Abstract: Laboratory demand management based on an IT-limiting management strategy or on education of the referring physicians appears helpful in maximising appropriate retesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In patients without diabetes and normal HbA 1c values, testing should be repeated at a minimum of 3-year interval [4]. Similar guidelines are available for the recommended intervals of repeat testing of many other laboratory parameters [44,45].…”
Section: A Re-testing Intervalsmentioning
confidence: 99%
“…In patients without diabetes and normal HbA 1c values, testing should be repeated at a minimum of 3-year interval [4]. Similar guidelines are available for the recommended intervals of repeat testing of many other laboratory parameters [44,45].…”
Section: A Re-testing Intervalsmentioning
confidence: 99%
“…Our study did not utilize a hard stop, which has been shown to be effective in reducing inappropriate vitamin D testing. 13,[15][16][17] By simply alerting a provider that a test may be inappropriate, our alert served as a soft stop, likely accounting for the limited efficacy despite using a more specific trigger for displaying the alert than has been reported previously. 4.…”
Section: Discussionmentioning
confidence: 95%
“…15,16 An inpatient alert in one report increased appropriate retesting of vitamin D from 40 to 64% by alerting providers if the vitamin D level had been checked recently. 17 Our study used a different method, with providers, receiving an alert only if the patient did not have an appropriate diagnosis for the ordering of vitamin D testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should emphasize that the effectiveness of the test is maximized when oriented to subjects suggestive or at risk for deficiency and low or absent when used as tool for screening or serial monitoring of vitamin intake or supplementation. In the latter case, to prevent retesting, a computer-based-limiting management strategy may be considered [95]. Finally, we should be aware that the recent recalibration of several commercial assays in view of harmonization policies is likely significantly shifting results and, if not correctly managed, potentially affecting the detection of folate deficiency in individuals at risk.…”
Section: Discussionmentioning
confidence: 99%